Modern Trends in the Armed Forces of Ukraine Transformation toward NATO Standards - Ordynovych, Andrii (Zenodo, 2020)
The article is concerned with the study of current trends which are applied by the Ukrainian Armed Forces on their way toward Euro-Atlantic Standards. The main purpose of this study is to underline the scope and main directions of the UAFs transformation agenda and critical challenges faced during introduction of the best practice and procedures into military service. The Ukrainian defence reform is expected to result in the establishment of effective, mobile defence forces, equipped with modern weapon systems, military and special hardware, able to guarantee national security and defense as well as provide an adequate and flexible response to military threats to the national security of Ukraine sustainably using the available operational (combat) capabilities and resources of the nation (1). The conducted study allowed determining the effect of transformation in the main dimensions of the Ukrainian Armed Forces development and finding out the points of cooperation with partner nations. In addition, the main challenges on the prospects of reform have been identified, among which there is a need to overcome the current autocracy and address demand for new type of leadership and quality of military personnel. It is concluded that new approaches have taken by the current Ukrainian Defense Authority opens a new window of opportunity to intensify reformation efforts, which will allow Armed Forces of Ukraine to meet NATO’s membership criteria as well as satisfy level of national security and defense in the most effective way. : {"references": ["How will the transition to NATO standards affect Ukraine\u02bcs defense capabilities: Conference, Gorshenin Institute, Ukraine. December 20, 2019. Available from https://armyinform. com.ua/tag/instytut-gorshenina. Ihor Kabanenko (2020). Ukraine's New National Security Strategy: A Wide Scope With Foggy Implementation Mechanisms. Eurasia Daily Monitor Volume: 17 Issue: 133. Retrieved September 24, 2020. Available from: https://jamestown.org/program/ukraines-new-national-security-strategy-a-wide-scope-with-foggy-implementation-mechanisms/. Lisbon Summit Declaration. Issued by the Heads of State and Government participating in the meeting of the North Atlantic Council in Lisbon. Issued on 20 November 20, 2010. Available from https://www.nato.int/cps/ en/natolive/official_texts_68828.htm. National Security Strategy and Strategic Defence and Security Review (2015). Retrieved June 02, 2020. Available from: https://www.gov. uk/government/publications/national-security-strategy-and-strategic-defence-and-security-review-2015 NATO Representation to Ukraine view on status and prospects of defense reform report #5, August 23, 2019, Kyiv. Ukrainian crisis media center (UCMC): Retrieved June 22, 2018 Available from: https://uacrisis.org/en/67656-ukraine-s-new-law-national-security-key-facts. Web-site of the Ministry of Defense of Ukraine, from https://defense-reforms.in.ua/"]}